Optimasi Penggunaan High Shear Mixer pada Pembuatan Fraksi Alkaloid dari Daun Awar-awar (Ficus septica) dengan Desain Faktorial - Kusnanto, Chelvin Ari; Gani, Andayana Puspitasari; Wahyuono, Subagus; Fakhrudin, Nanang (Pusat Penelitian dan Pengembangan Biomedis dan Teknologi Dasar Kesehatan, 2021)
Awar-awar (Ficus septica) is an Indonesian anticancer plant that contains alkaloids as the active compound. The n-hexane insoluble fraction (FTLH) is alkaloid-containing fraction obtained from the ethanolic extract of F. septica leaves (EEDFS) by fractionation using n-hexane. High shear mixer (HSM) can be used to optimize the separation processes, including fractionation. The application of HSM in the fractionation of EEDFS is affected by fractionation duration, amount of solvent per gram extract, and strirring strength. Thus, these parameters must be optimized to obtain the optimum condition for the production of FTLH with the highest alkaloid content. This study aimed to optimize the production of FTLH using HSM with factorial designs. The single factor experimental design was employed to determine the influence of the individual variable on the alkaloid content and to define the optimum range value of each variable. A full factorial design was used to determine the presence of interaction among the factors and to determine the optimal fractionation condition. The results showed that all investigated factors independently affected alkaloid contents. The solvent volume of 14-18 mL per gram extract, the fractionation duration of 2.5-5.0 minutes, and the stirring strength of 3000 rpm are the optimal range value of each factor. The optimal conditions were solvent volume of 14.0-14.4 mL/gram extract, fractionation duration of 2.5-2.7 minutes, and strirring strength at 3000 rpm. At the optimal condition, the total alkaloid content in the FTLH reached 0.1466% or 1.3 times higher than the extract (0.1128%).